Optimal Student Loans and Graduate Tax under Moral Hazard and Adverse Selection - Robert J. Gary-Bobo; Alain Trannoy (Center for Economic Studies and ifo Institute (CESifo), 2013)
We completely characterize the set of second-best optimal menusof student-loan contracts in a simple economy with risky labour-market outcomes, adverse selection, moral hazard and risk aversion. The model combines structured student loans and an elementary optimal income-tax problem à la Mirrlees. This combination can be called a graduate tax. There are two categories of second-best optima: the equal treatment and the separating allocations. The equal treatment case is obtained when the social weights of student types are close to their population frequencies; the expected utilities of different types are then equalized, conditional on the event of success on the labor market. But individuals are ex ante unequal because of differing probabilities of success, and ex post unequal, because the income tax trades o incentives and insurance (redistribution). In separating optima, the talented types bear more risk than the less-talented ones; they arise only if the social weight of the talented types is sufficiently high. The second-best optimal graduate tax provides incomplete insurance because of moral hazard; it typically involves cross-subsidies; generically, it cannot be decomposed as the sum of an optimal income tax depending only on earnings, and a loan repayment, depending only on education. Therefore, optimal loan repayments must be income-contingent.
Keywords: D60; D82; H21; I22; I24; 330; student loans; graduate tax; optimal income tax; adverse selection; moral hazard; risk